Country Partnership Framework for Uzbekistan for the Period FY16-FY20 - World Bank; International Finance Corporation; Multilateral Investment Guarantee Agency (World Bank, Washington, DC, 2016)
This Country Partnership Framework (CPF) covers the five-year period FY16-20. Anchored in the government’s medium-term development plan as outlined in a January 2015 Cabinet of Ministers Program of Action, it also reflects the analysis and recommendations of the World Bank Group’s (WBG) 2015 Systematic Country Diagnostic (SCD) for Uzbekistan and the lessons learned from the Completion Report of the previous CPS. The CPF’s objectives and program, which focus on developing the conditions for faster job creation, are consistent with the WBG’s twin goals of eliminating extreme poverty and boosting shared prosperity. The Uzbekistan Systemic Country Diagnostic (SCD) identified ten priority areas that would need to be addressed to eliminate poverty, boost shared prosperity, and enable Uzbekistan to reach upper middle-income status. The government’s strategic objectives are for Uzbekistan to achieve upper middleincome status by 2030, implying income growth averaging 6 percent annually, and in particular to create 500,000 jobs annually. Building country systems for statistical, fiduciary, safeguard, and statistical capacity underlie the foundation of this CPF. The CPF program will remain flexible as circumstances change and new opportunities may arise.